Assessing the effect of airport physical environment on passenger's satisfaction: a mediating effect of passenger's delight / Nur Aida Amani Baharuddin and Mazlina Mahdzar. - Baharuddin, Nur Aida Amani; Mahdzar, Mazlina (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
In tourism development, the impact of demand for air transport by travelers is affecting new forms of tourism and new destinations. The airport is a consistent growth segment in the tourism industry and transportation. The objective of the proposed study is to investigate the influence of physical environment of the airport on passengers’ delight and satisfaction. Studies on the physical environment impact on customer delight and satisfaction are still limited, especially in the context of international airports. In order to understand this phenomenon, the study examines the literature, raises issues and develops the framework within the research context. The study will opt a convenience sampling method, with a total of 400 sets of questionnaires will be distributed to local and international passengers at Kota Kinabalu International Airports (KKIA). This study provides theoretical basis for future research on the role of physical environment of international airports and its impact on passengers’ emotions and behavior. It also assists international airport industry practitioners to better understand how airport physical environments affects passengers’ experience and satisfaction.